2002
DOI: 10.1128/jb.184.2.525-530.2002
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin and GroESL Modulate In Vitro Activity of NodD

Abstract: In the early stages of symbiosis between the soil bacterium Sinorhizobium meliloti and its leguminous host plant, alfalfa, bacterial nodulation (nod) genes are controlled by NodD1, NodD2, and NodD3, members of the LysR family of transcriptional regulators, in response to flavonoid and other inducers released by alfalfa. To gain an understanding of the biochemical aspects of this action, epitope-tagged recombinant NodD1 and NodD3 were overexpressed in Escherichia coli. The DNA binding properties of the purified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 41 publications
1
39
0
Order By: Relevance
“…Although all the three operons are heat inducible and mediated through the CIRCE elements, differential levels of expression have been demonstrated; the essential chaperonin groEL1 shows the highest induction followed by groEL2 (Rodriguez-Quinones et al 2005). On the other hand, induction of groEL3 is very low following heat shock, but higher levels are observed under anaerobic conditions and in the presence of NifA (Rodriguez-Quinones et al 2005;Yeh et al 2002). Sequence analysis followed by detailed promoter probe assays revealed that the groEL1 operon is regulated by RpoH-and HrcA-dependent mechanisms while groEL2 appears to be solely regulated by RpoH.…”
Section: Multiple Chaperonins In Rhizobium-the Division Of Labor Situmentioning
confidence: 97%
See 2 more Smart Citations
“…Although all the three operons are heat inducible and mediated through the CIRCE elements, differential levels of expression have been demonstrated; the essential chaperonin groEL1 shows the highest induction followed by groEL2 (Rodriguez-Quinones et al 2005). On the other hand, induction of groEL3 is very low following heat shock, but higher levels are observed under anaerobic conditions and in the presence of NifA (Rodriguez-Quinones et al 2005;Yeh et al 2002). Sequence analysis followed by detailed promoter probe assays revealed that the groEL1 operon is regulated by RpoH-and HrcA-dependent mechanisms while groEL2 appears to be solely regulated by RpoH.…”
Section: Multiple Chaperonins In Rhizobium-the Division Of Labor Situmentioning
confidence: 97%
“…Further, purified GroEL3 has been demonstrated to assist assembly of the NodD complex from its constituents Nod1, 2, and 3 (Ogawa and Long 1995), and co-expression of GroEL3 in E. coli improved folding and assembly of the NodD (Yeh et al 2002), analogous to the GroEL-dependent functional regulation of LuxR of Vibrio fischeri (Dolan and Greenberg 1992). Moreover, expression of nod genes and groEL3 has been shown to be co-regulated with HrcA-like mechanism (Gould et al 2007a, b).…”
Section: Multiple Chaperonins In Rhizobium-the Division Of Labor Situmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant bZIP16-his6 protein was expressed in Escherichia coli and purified in its native form with use of nickel-nitrilotriacetic acid agarose following the manufacturer's protocol (Novagen). EMSA was conducted as described (Yeh et al, 2002) with minor modification. In brief, the recombinant protein and 39-end biotinlabeled G-box were coincubated at room temperature for 10 min in binding buffer (115 mM Tris-HCl, pH 7.5, 10 mM EDTA, 1 mM DTT, 50% glycerol, 0.5 mg/mL BSA, 0.5 mg/mL poly dI-dC, and 3 mM NaCl).…”
Section: Emsamentioning
confidence: 99%
“…Thus, 1 of the B. japonicum groE operons is regulated by NifA, and a reduction in the overall level of chaperonin expressed in this organism leads to a defect in nitrogen fixation caused by severely reduced levels of some nitrogenase enzymes (Fischer et al 1993(Fischer et al , 1999. In S. meliloti, mutations in 1 of the groE operons leads to the formation of ineffective nodules, and it has been shown that 1 of the GroEL proteins interacts with the NodD activator proteins as well as having a role in quorum sensing (Ogawa and Long 1995;Yeh et al 2002;Marketon and Gonzalez 2002).…”
Section: Introductionmentioning
confidence: 99%